Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 13: Western Australian species of Bubocorophiina in Rhinoecetes, Cephaloecetes, Sinoecetes, Borneoecetes and Pararhinoecetes gen. nov. - Just, Jean (Zootaxa, 2019)
The Western Australia fauna of Bubocorophiina (Siphonoecetini) from the Albany area in the south to Port Hedland in the north-west, a coastal stretch of about 2000 km, is reported. One new genus and 11 new species are described: Rhinoecetes sinuduopopulus sp. nov., R. rockinghamia sp. nov., R. makritrichoma sp. nov., R. lowryi sp. nov., R. caetus sp. nov., R. karkharius sp. nov., R. wamus sp. nov., R. setosus sp. nov., Borneoecetes minimus sp. nov. (first record of Borneoecetes Barnard & Thomas, 1984 from Australia); Sinoecetes reni sp. nov. (first record of Sinoecetes Ren, 2012 from Australia), and Pararhinoecetes bicornis gen. et sp. nov. In addition, Cephaloecetes enigmaticus, previously described from the southeast coast of Australia, is recorded in the Albany area. A key to Western Australian Bubocorophiina is presented, and the distribution around Australian of the genera in the subtribe is commented upon.